The Alumni Exhibition - Davidson, Julia; Kelly, Gemey; Peters, David; Stevenson, Sheila (Halifax : Anna Leonowens Gallery - Nova Scotia College of Art and Design, 1983)
Annett, Meredith ; Armstrong, Lesley G. ; Berkelaar, Marretje ; Biggs, Beth ; Birdsall, Pamela ; Brownlee-Ramsdale, Sandra ; Cochrane, Bruce ; Greenwell, Gloria ; Landry, Wendy S. ; MacLachlan, Susanne ; Pavey, Karin ; Porter, Kim ; Sekerak, Steve ; Swim, Peter B. ; etc.
The Alumni Exhibition, Anna Leonowens Gallery - Nova Scotia College of Art and Design, Halifax, October 1-22, 1983
boek